Transcriptional changes during isoproterenol-induced cardiac fibrosis in mice - Nanda, Disha; Pant, Priyanka; Machha, Pratheusa; Sowpati, Divya Tej; Kumarswamy, Regalla (Frontiers in Molecular Biosciences, 2023)
β-adrenergic stimulation using β-agonists such as isoproterenol has been routinely used to induce cardiac fibrosis in experimental in animal models. While transcriptome changes in surgical models of cardiac fibrosis such as Transverse aortic constriction (TAC), and coronary artery ligation (CAL) are well-studied, transcriptional changes during isoproterenol induced cardiac fibrosis is not well explored.Cardiac fibrosis was induced in male C57BL6 mice by administration of isoproterenol for 4, 8or 11 days at 50mg/kg/day dose. Temporal changes in gene expression were studied by RNA sequencing.We observed a significant alteration in the transcriptome profile across the different experimental groups compared to the saline group. Isoproterenol treatment caused upregulation of genes associated with ECM organization, cell-cell contact, three-dimensional structure, and cell growth, while genes associated with fatty acid oxidation, sarcoplasmic reticulum calcium ion transport, and cardiac muscle contraction are downregulated. A number of known long non-coding RNAs (lncRNAs) and putative novel lncRNAs exhibited differential regulation.In conclusion, our study shows that isoproterenol administration leads to the dysregulation of genes relevant to ECM deposition and cardiac contraction and serves as an excellent alternate model to the surgical models of heart failure.